PURCHASE DECISION BETWEEN CONSUMER LOYALTY AND BRAND IMAGE - Kasiman; Anastasia Maria H (MBA - Journal of Management and Business Aplication, 2020)
This study aims to determine and analyze the effect of consumer loyalty and brand image onseafood food purchasing decisions. The analytical tool used in this study is multiple linearregression analysis, T-Test and F-Test and Determination Coefficient. With SPSS The resultsof the research show that partially consumer loyalty and brand image influence the decisionto buy seafood. Likewise, the results of other hypothesis tests indicate that simultaneously theindependent variable of consumer loyalty and brand image influences buying decisions. Thusthe results of this hypothesis test are in line with several previous studies. Consumer loyalty isthe commitment of customers to a brand, store, or supplier based on the very positive natureof long-term purchases, whereas brand image states that a brand has strong roots when thebrand is associated with values that represent or are desired by consumers.